Menguji Batas Business Judgement Rule: Studi Kasus Pengembangan Bisnis Lng PT Pertamina di Amerika Serikat - Budi Tri Wijayanto; Siska Dwi Andini (Jurnal Syntax Admiration, 2024)
Business decisions made by the directors of a company are often the subject of legal interpretation, especially when the decision results in losses to the company or the state. This research focuses on the application of the Business Judgement Rule (BJR) principle in the case of LNG business development by PT Pertamina in the United States involving Karen Agustiawan as President Director. Through a normative juridical approach and qualitative analysis, this study evaluates the extent to which the BJR can protect the board of directors from lawsuits as well as identify the factors that cause the decision not to be protected by the BJR principle. The results of the analysis show that the application of BJR cannot provide legal protection if the business decision is not based on good faith, prudence, and without conflict of interest. In this context, the study also discusses the application of progressive legal theory as an alternative framework for handling this kind of case. The study recommends strengthening regulations to set limits on BJR implementation and ensure transparency in the business decision-making process.